Identification of the Slovak traditional cheese “Parenica” microflora - Kačániová, Miroslava; Terentjeva, Margarita; Kunová, Simona; Nagyová, L’udmila; Horská, Elena; Haščík, Peter; Kluz, Maciej; Puchalski, Czeslaw (Acta Agraria Debreceniensis, 2018)
Numerous studies have demonstrated the higher accuracy, faster time-to-results and lower costs provided by MALDI Biotyper systems compared to classical methods. In this study, the culturable population of total count of bacteria, enterococci, coliforms bacteria, lactic acid bacteria (LAB) and microscopic fungi and yeasts from cow’s dairy products was identified using the MALDI-TOF MS Biotyper. Altogether, 50 samples of the Slovak cheese “Parenica” were examined. Total numbers of bacteria were cultured on Plate count agar at 37 °C for 24–48 h, aerobically; enterococci were cultured on Enterococcus selective agar at 37 °C for 24–48 h, aerobically; coliforms bacteria were cultured on Violet Red Bile lactose agar at 37 °C for 24–48 h, aerobically. The LAB were cultured on MRS (Main Rogosa agar), MSE and APT agar at 30 °C in microaerophilic conditions. The microscopic fungi and yeasts were cultured on Malt extract agar at 25 °C for 5 days, aerobically. Isolated strains (total 669) were subjected to identification by the MALDI-TOF MS. Among total count the identified bacteria mostly were Acinetobacter baumannii, Bacillus cereus, Micrococcus luteus and Staphylococcus warneri. Escherichia coli and Enterobacter cloacae were the most abundant coliform bacteria representatives identified. Coliform bacteria included Citrobacter, Hafnia and Klebsiella. Altogether three genera belonged to the LAB – Lactobacillus, Lactococcus and Leuconostoc were identified with Lactococcus lactis, Lactobacillus plantarum, Lactobacillus coryniformis, L. fructivorans and Leuconostoc mesenteroides were considered as the dominated LAB species in dairy products. Among yeasts, Kluyveromyces lactis, Candida zeylanoides and Yarrowia lipolytica were among the most isolated.